Integration of Life Skills in Volleyball Extracurricular Activities in Elementary Schools - Diansyah, Rival; Muhtar, Tatang; Sudrazat, Adang (Indonesian Journal of Sport Management, 2024)
This research analyses the influence of life skills integration in volleyball extracurricular activities at Sindangwangi State Elementary School. The research method used was true-experimental with a pretest-posttest control group design. The sample in this study was 38 students at Sindangwangi State Elementary School, Sumedang Regency, who took part in extracurricular volleyball in the age range of 11-12 years using a purposive sampling technique. It is divided into two groups: the Experimental group, which was given treatment to as many as 19 students, and the Control group, which did not treat as many as 19 students. The instrument used in this research is the Life Skills Scale of Sport (LSSS) developed by Cronin & Ellen, which measures eight life skills with a 47-item assessment scale. From the results of this research, it can be concluded that the average value of the Experimental and Control groups has a different average value, namely 66.47% > 38.53%, which means the average value in the Experimental group (Integration of Life Skills) is greater than the average value of the group. Control is stated that life skills integration is quite effective in the results of elementary school students' volleyball extracurricular activities.